Rate enhancement in palladium catalyzed Heck reactions by Lewis acid promoters - Sud, Abhishek; Deshpande, Raj Madhukar; Chaudhari, Raghunath V. (Catalysis Communications, 2007)
Significant enhancement in the rate of Heck reactions has been achieved when catalytic amounts of Lewis acid (like FeCl(3)) promoters in the presence of trace amounts of water (> 2000 ppm) are used along with Pd complex catalysts. Experiments with different aryl halides, bases as well as olefins have been carried out to demonstrate the role of Lewis acid promoters. The increase in the reaction rates is due to the weakening of Ar-X bond by the Lewis acid in the manner similar to Friedel-Crafts reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Heck reaction; Lewis acid; Palladium; Promoters